Syntheses and evaluation of novel 3-hydroxy-1,3-diaryl-2,3,5,6,7,8-hexahydro-imidazo[1,2-a]pyridine-1-ium bromides as potential anticancer agents - Sergii Demchenko; Sergii Yarmoluk; Volodymyr Sukhovieiev; Oleksandr Golovchenko; Oleksandr Sukhovieiev; Anatolii Demchenko (Pensoft Publishers, 2024)
New 3-hydroxy-1,3-diaryl-2,3,5,6,7,8-hexahydro-imidazo[1,2-a]pyridine-1-ium bromides have been designed, synthesized, and characterized by 1Н NMR, 13C NMR, and LCMS. The cyclic structure of the condensation products of aryl-(3,4,5,6-tetahydropyridin-2-yl)amines with α-bromoketones has been proven. It has been shown that heating 3-hydroxy-1,3-bis-(41-methoxyphenyl)-2,3,5,6,7,8-hexahydro-imidazo[1,2-a]pyridine-1-ium bromide in acetic anhydride accompanied by elimination of water to form 1,3-bis-(41-methoxyphenyl)-5,6,7,8-tetrahydro-imidazo[1,2-a]pyridine-1-ium bromide. Antitumor activity of 1,3-bis-(41-ethoxyphenyl)-3-hydroxy-2,3,5,6,7,8-hexahydro-imidazo[1,2-a]pyridine-1-ium bromide and 1,3-bis-(41-methoxyphenyl)-5,6,7,8-tetrahydro-imidazo[1,2-a]pyridine-1-ium bromide have been studied. The fully aromatic imidazo[1,2-a]pyridine-1-ium bromide system was shown to have a higher antitumor effect. According to the screening results, the tested compound showed a significant level of anticancer effect on cancer cells of colon COLO 205 (lgGI50 = -5.35, lgTGI = -4.70 and lgLC50 = -4.19) and melanoma SK-MEL-5 (lgGI50 = -5.57, lgTGI = -4.81 and lgLC50 = -4.17).